Problems of Improving the Physical Status of Preschool Children - Khankeldiyev Sher Khakimovich (Genius Journals, 2022)
The introduction of modern educational programs and technologies into the educational process, aimed at the comprehensive intellectual, spiritual, aesthetic and physical development of children, a radical increase in the level of preparation of children for school
Keywords: modern educational programs; educational process; comprehensive intellectual; spiritual